PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN, TRUST, DAN WORD OF MOUTH PADA PT. BANK BPD BALI CABANG KARANGASEM - Cahyadi, Putu Budi; Wardana, I Made; Nurcahya, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
The research aimed to examine the influence of service quality on satisfaction, trust, and WoM customers of PT. Bank BPD Bali Karangasem branch. Respondents were 180 people, with the criteria that the customer has a savings account or a credit. Sampling was conducted in two stages, by combining purposive sampling with convenience sampling. Structural Equation Model (SEM) is used as an analytical technique, in combination with the use of AMOS applications and SPSS. AMOS Text Output indicates that the influence of service quality on satisfaction, satisfaction to trust, satisfaction with WOM, as well as the trust of the WOM, is positive and significant. Keywords : wom, satisfaction, trust, quality of service
Keywords: kualitas layanan; kepuasan; trust; word of mouth